Estudo da aplicação da técnica de Trabalho Essencial da Fratura (EWF) na análise da tenacidade à fratura de sistemas poliméricos - Finocchio, Henrique (2013)
Polymeric materials, including polymer blends and composites are used in a great variety of engineering applications. Toughness, which is associated to the capacity of the material to absorb energy before its break, is frequently an important characteristic to many high-performance applications becoming essential the use of effective methods to determine the intrinsic toughness of a material in order to increase the possibility of development and applications concerning polymeric materials establishing a relationship between fracture behavior and morphology. The method Essential Work of Fracture (EWF) has been receiving special attention to determine the toughness of high ductility polymers, however, sometimes, a low discerning use of the technique concerning the theory and the correct preparation of specimen of polymeric systems.This way, it was developed a very selective procedure to the preparation specimen which is the main step to obtain precise results. In order to expand EWF technique application and to evaluate the fracture toughness, in this work the fracture behavior of three different polymeric systems was observed. Two of them showed an excellent response to the technique. The nanocomposites of blends HDPE/LLDPE and OMMT and Polypropylene/Glass Fiber composites, both semi-crystalline materials, with ductile behavior. On the other hand, observing the other system, nanostructured blends SAN/PBT, with brittle behavior, the EWF method applied in this work showed to be inappropriate. Therefore, there was an improvement concerning the understanding of limitations and peculiarities of the EWF technique, which is nowadays a very useful tool to characterize the toughness of ductile polymeric materials althought it still has some limitations related to brittle materials.